2020
DOI: 10.3390/ijerph17072541
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Nicotine Delivery Systems (ENDS) in China: Evidence from Citywide Representative Surveys from Five Chinese Cities in 2018

Abstract: China is the largest cigarette consuming country in the world. The emergence of electronic nicotine delivery systems (ENDS) in China may have important implications for the Chinese tobacco market. Unfortunately, research on ENDS in China, while growing, is still limited. This study was designed to examine the awareness and use of ENDS among adult urban residents in China. Data from five citywide representative surveys conducted in 2017–2018 were used. Percentages of residents who had ever heard of, ever used, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 38 publications
3
22
0
Order By: Relevance
“…For instance, consider the landscape of e-cigarette use in China, the first epicentre of COVID-19. A 2018 survey of 10 233 individuals in five Chinese cities found that only 0.9% had used e-cigarettes within the past 30 days [ 5 ]. Only 0.2% of those 65 years and older reported e-cigarette use within the past 30 days compared to 1.5% of those in the 15–24 year age range.…”
mentioning
confidence: 99%
“…For instance, consider the landscape of e-cigarette use in China, the first epicentre of COVID-19. A 2018 survey of 10 233 individuals in five Chinese cities found that only 0.9% had used e-cigarettes within the past 30 days [ 5 ]. Only 0.2% of those 65 years and older reported e-cigarette use within the past 30 days compared to 1.5% of those in the 15–24 year age range.…”
mentioning
confidence: 99%
“…Our study results revealed that a significant proportion of Chinese smokers believed e-cigarettes were linked with smoking cessation. Chinese smokers' perception of the potential role of e-cigarettes in aiding cessation was likely the result of exposure to e-cigarette advertising, which often contained unsubstantiated claims about the e-cigarette's effectiveness in helping smokers quit and its role as a better and healthier substitute for cigarettes 17,33,34 . As China increases its effort to promote smoking cessation 35,36 , it is expected that more Chinese smokers will seek to quit smoking, and some of these smokers may start to use e-cigarettes as a result, similar to what has been observed in the US and UK.…”
Section: Discussionmentioning
confidence: 99%
“…Multi-stage cluster sampling was applied to generate a citywide representative sample for each city following the guidelines of the Sample Design Manual of GATS 25 . Detailed study design and sampling methods can be found in a previously published study using the TQS data 17 . A total of 8043 participants completed the TQS survey in all four cities.…”
Section: Study Design Setting Participantsmentioning
confidence: 99%
See 2 more Smart Citations